Efektivitas Nature Music Theraphy Terhadap Peningkatan Konsentrasi Belajar Mahasiswa - Adissah Putri Herdianti; Khairiah Rawita; Ramilah Suta; Dwi Aristawidya R; Prima Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Concentration is an important aspect of learning, but there are still many students who experience difficulty concentrating. This research aims to determine the effect of nature music therapy on increasing student learning concentration. This experimental research uses a pretest-posttest control group design. The sample consisted of 10 students who were divided into experimental and control groups. Concentrations were measured before and after treatment. The result was that there was a higher average increase in the experimental group's concentration score (sig value = 0.011; two-sided p (p<0.05)). Therefore, it can be concluded that nature music therapy has a positive and significant influence on increasing student learning concentration.